Effect of Different Crown Cap Closures on Phenolics and Sensory Attributes of Bottle-Fermented Sparkling Wines - Minnaar, P.P.; Gerber, P.; Booyse, M.; Jolly, N. (South African Journal of Enology and Viticulture, 2025)
Bottle-fermented sparkling wines closed with crown caps of different O2 permeabilities while ageing on the yeast lees were investigated for their effect on phenolics and sensory attributes. The crown caps were denoted as reference (least permeable), Crown++ (intermediate permeability) and Crown+ (most permeable) to oxygen. Total phenolics and physiochemical parameters were measured using a spectrophotometric technique and infrared spectrometry, respectively. Individual phenolics were quantified using an HPLC technique. Dissolved oxygen was not significantly different between Crown+ and Crown++ wines. Crown+ wines were approx. 2% higher in flavan-3-ols than Crown++ wines and flavonols were approx. 8% higher in Crown+ wines than Crown++ wines. Total phenolic acids were approx. 3% higher in Crown+ wines than Crown++ wines. Gallic, caftaric, and caffeic acids were not significantly different between Crown+ and Crown++ wines, whereas p-coumaric acid was reported to be approx. 6.6% higher in Crown+ wines. Reference wines were associated with short aftertaste, bruised apple, small bubbles, toasty, and more autolysis flavours. Crown+ wines were associated with few bubbles, balanced acidity, fruity, full-bodied, intense aroma, and yeasty, whereas Crown++ wines had varying associations with large and numerous bubbles, less autolysis, thin, shy nose, but persistent aftertaste. Differences in phenolic concentrations and sensory attributes could be ascribed to oxygen variability in the wines as a result of the different closures. Based on the sensory profile, it is concluded that the Crown+ wines had the most favourable sensory attributes and are therefore the most suitable closure for base wine after 43 months on the yeast lees. The use of more or less permeable crown caps during the production of bottle-fermented sparkling wines can be a tool for a desired sensory outcome.